In vitro effect of amorphous calcium phosphate paste applied for extended periods of time on enamel remineralization (Journal of Applied Oral Science, 2017)
Dental applications based on the unique characteristics of amorphous calcium phosphate stabilized by casein phosphopeptides (CPP-ACP) have been proposed, as well as the improvement of its properties. Objectives: The objective of this study was to determine the ability of topically applied CPP-ACP from a commercial product to remineralize subsurface lesions when applied for extended periods of time (3 h and 8 h). Material and Methods: Artificially induced carious lesions were produced in 50 bovine enamel blocks previously selected by surface hardness. After treatments with gel without F and CPP-ACP applied for 1 minute (Placebo); 2% NaF neutral gel applied for 1 minute (Fluoride 1 min); CPP-ACP applied for 3 min (ACP 3 min); and CPP-ACP applied for 3 h (ACP 3 h) and for 8 h (ACP 8 h), the enamel blocks were submitted to the remineralization pH-cycling. Surface hardness and synchrotron micro-tomography were used to determine the percentage of surface hardness recovery (%SHR) and to calculate mineral concentration (gHAp.cm−3), respectively. The data were submitted to ANOVA followed by the Student-Newman-Keuls test (p